The Effects of Learning Media Lectora Inspire of Indonesian Plurality Material on the Results of Learning Social Studies Affective Tolerance at the SMPN 1 Krembung - Albariki, Ahmad Yazid; Prasetyo, Ketut; Sunarto, Sunarto (International Journal for Educational and Vocational Studies, 2020)
This study aims to analyze the effect of the use of the Lectora Inspire learning media on the plurality of Indonesian society towards the results of the learning of the affective domain of tolerance in social studies at SMPN 1 Krembung. This research uses quantitative research methods with experimental patterns. The research data obtained are; First, the questionnaire data used the Paired Sample t-test showing the result of the sig. (2-tailed) value of 0,000 < 0,05 which means that H0 was rejected H1. Second, the questionnaire data using Independent Sample t-test showed the results of 3,163 > 2,000 which showed the results of tcount > ttable with a significance value Î± < 0,05, i.e. sig. (2-tailed) 0,001 < 0,05 which means that H0 is rejected and H1 is accepted. Based on the results of data analysis, it can be concluded that there are significant differences in the affective domain of student learning outcomes between students before and after treatment and posttest results after being treated in the experimental class are higher than the posttest results. in the control class, which means that there are significant differences in learning outcomes from the affective domain of student tolerance between the experimental class using the Lectora Inspire learning process and the control class using image media.